Postnatal development of the epididymis from birth until puberty of indigenous sheep (Barind-type) in Bangladesh (Journal of Advanced Veterinary and Animal Research, 2026)
Objectives: The present study investigated the biometrical and histomorphometric changes in the epididymis of Barind-type indigenous sheep during postnatal development from birth to puberty. Materials and Methods: A total of 21 Barind-type indigenous lambs of varying postnatal ages—day 0, 1, and 2 weeks; and 1, 2.5, 5, and 7 months—were used in this study. Histomorphometric analysis was done using routine haematoxylin and eosin staining. Results: The Barind-type indigenous ram lamb epididymis followed a regionalized pattern of development, with the tail beginning development before other anatomical regions. The Barindtype indigenous ram lamb epididymal development was slow until 1 month of age, followed by a rapid period of epididymal development. The epididymal length and weight were more than 5 and 50 times greater, respectively, at puberty than at birth. The epithelial height and tubular diameter were expanded significantly (p < 0.05) from 1 month of age in all regions except in the tail at 7 months, where the epithelial height decreased dramatically (p < 0.05). Regarding regional differences, the largest epithelium height and tubular diameter were consistently found in the tail, and the smallest in the head, until 5 months. At 7 months, the reverse was observed in epithelium height. Epididymal regions were significantly (p < 0.05) different from one another at 5 and 7 months in terms of tubular diameter and epithelium height, respectively. Sperm first appeared in the tubular lumen by 7 months in the Barind-type indigenous ram epididymis. Conclusion: The biometric and histomorphometric alterations in the epididymal structure of Barind-type indigenous ram during postnatal development until puberty are recorded for the first time in this study.J. Adv. Vet. Anim. Res., 12(4): 1115–1124, December 2025http://doi.org/10.5455/javar.2025.l972